National Competencies for Registered Nurses in Primary Care: A Delphi Study. (December 2020) - Lukewich, Julia; Allard, Michelle; Ashley, Lisa; Aubrey-Bassler, Kris; Bryant-Lukosius, Denise; Klassen, Treena; Magee, Tanya; Martin-Misener, Ruth; Mathews, Maria; Poitras, Marie-Eve; Roussel, Josette; Ryan, Dana; et al.
A Delphi (consensus) process was used to obtain national agreement on competencies for registered nurses (RNs) in primary care. A draft of competencies was developed by key informants. Following this, nurses with primary care experience/expertise completed a Delphi survey to rate the importance of competency statements on a six-point Likert scale. Statements not reaching consensus (agreement ≥80%) were modified and included in a second (final) round. The first survey was completed by 63% ( n = 86/137) of participants and 84% ( n = 72/86) of these participants completed the second survey. Most statements ( n = 45) achieved agreement after the first survey; one statement was dropped and two were combined following the second round. The final list of competencies consists of 47 statements across six domains (professionalism; clinical practice; communication; collaboration and partnership; quality assurance, evaluation, and research; leadership). National competencies will help strengthen the RN workforce within primary care, improve team functioning, and support role integration/optimization.